African stories - Hull, Robert (Wayland Hove, 1992)
"African Stories" by Robert Hull, published in 1992. This 48-page hardcover book is part of the "Tales from Around the World" series and offers a collection of myths, legends, and traditional stories from various African cultures. The narratives are accompanied by both color and black-and-white illustrations by Peter Kettle, providing readers with a visual and cultural context. Given its publication date, the book provides historical context up to the early 1990s. For more recent information on African stories, additional sources would be beneficial.